On groups with many normal subgroups - Alessio Russo; Mario Viscusi (International Journal of Group Theory)
The structure of groups which are rich in normal subgroups has been investigated by several authors. Here, we prove that if a radical group G has normal deviation, which means that the set of its non-normal subgroups satisfies a very weak chain condition, then either G is a minimax group or all its subgroups are normal.